1975
DOI: 10.3109/00048677509159841
|View full text |Cite
|
Sign up to set email alerts
|

The Infant Development Distress (IDD) Syndrome: A Predictor of Impaired Development?

Abstract: A group of eight infants with a disorder termed the IDD syndrome and another group of eight matched healthy infants taken into study at the same time have been followed-up for 6.75 years. The follow-up technique and some findings are described. Three IDD syndrome children are still severely disturbed. Three others show recovery from severe developmental disturbance. But one child who was grossly abused after being taken into the study has been well since the third follow-up. The comparison children have not ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 2 publications
0
14
0
1
Order By: Relevance
“…Engel (1962) considers Depression -Withdrawal as the "more undifferentiated affect warning of loss of supplies and indicating the need for conservation of energy" (p. 95). Ironside (1975) described it as a biological process subserving survival and reality based discouragement. Menahem (1984) described two infants with possible Conservation -Withdrawal reaction arising from grossly inadequate feeding and suggested that many infants with NOFTT can be better understood within the concept of Conservation -Withdrawal.…”
Section: From Sustained Withdrawal Reaction To Depression In Infantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Engel (1962) considers Depression -Withdrawal as the "more undifferentiated affect warning of loss of supplies and indicating the need for conservation of energy" (p. 95). Ironside (1975) described it as a biological process subserving survival and reality based discouragement. Menahem (1984) described two infants with possible Conservation -Withdrawal reaction arising from grossly inadequate feeding and suggested that many infants with NOFTT can be better understood within the concept of Conservation -Withdrawal.…”
Section: From Sustained Withdrawal Reaction To Depression In Infantsmentioning
confidence: 99%
“…No matter how early it may begin, it is the result of psychic work, leading to the maintenance of a sort of Depressive Object (Denis, 1987). Thus it may be important to identify infant withdrawal behavior as an alarm distress symptom before it becomes obvious (Ironside, 1975).…”
Section: Infant Withdrawal In the Process Of Evaluationmentioning
confidence: 99%
“…The link between depression-withdrawal reaction in infants and learned helplessness behavior was made relatively recently ͑Seligman, 1975; Ironside, 1975;Widlöcher, 1983;Menahem, 1984;Lask, Britter, Kroll, Magnana, & Tranter, 1991;Nunn & Lynne Thompson, 1996;Teti & Gelfand, 1997͒. In a now ethically disputable experiment, the famous Learned Helplessness situation, a dog was electrically shocked while in an inescapable situation, which led to resignation, thus leading to the model of Learned Helplessness as the basis for depression, and to the use of the Learned Helplessness paradigm as a key screening test for antidepressant Depression in infants • activity ͑Seligman, 1975͒.…”
Section: Animal Models Of Depressionmentioning
confidence: 99%
“…This can be observed in the "still-face" experiment (Cohn & Tronick,1983;Field, 1984;Seifer & Dickstein, 1993;Tronick & Weinberg, 1997), in studies of the effect of maternal depression (Murray & Cooper, 1997), or in parents who have other kinds of mental impairment (Reder & Lucey, 1995). Severe withdrawal can be observed also at different levels in infants with Anxiety Disorders, Post Traumatic Stress Disorders (Zeanah, 1993), and in children who have suffered from chronic and severe pain in infancy (Gauvain-Piquard, Rodary, Rezvani & Lemerle, 1987;Gauvain-Piquard, Rezvani, Rodary & Serbouti, 1999).Although withdrawal is a very important alarm signal (Ironside, 1975), no assessment tool is available to date, to our knowledge. This article describes the construction and the validation of a scale, the Alarm Distress Baby Scale (ADBB), designed to assess sustained withdrawal reactions in infants aged between 2 -24 months.…”
mentioning
confidence: 99%